Player Tracking using Ultrawideband - João Miguel Bagoim Guimarães Ferreira Bernardo (2017)
Nowadays player detection, labelling and tracking in a field is done by using cameras and video analysis or by GPS-based systems to give managers and viewers statistics about each player. But those approaches aren't always reliable. This thesis is about building a system using time-of-flight radio transmitters (DWM1000 Module by decaWave will be used for this) to give a more precise estimation for the position of each player at any given point in time. Part of this task involves the creation of firmware for the communication between each transmitter and an information system to collect the data and process it for better understanding of each individual performance in the field. The purpose of this is to create a more accessible tracking system to be used in training or official games as some of the alternatives are either too expensive or too complicated to use. To validate the reliability of such a system first some tests with a measurement tape will be made to confirm, and adjust if necessary, the algorithm that calculates the distances to a single player. After that two teams of futsal players will be utilized in order to test the fully developed system and correct any errors that might exist.